2014
DOI: 10.4314/jae.v18i1.13
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Rice Technologies Introduced by the United States Agency for International Development in Anambra and Ebonyi States, Nigeria

Abstract: The study determined the levels of adoption of improved rice technologies introduced by USAID MARKETS project phase one in Anambra and Ebonyi States, Nigeria. The population of the study included all project participant rice farmers of USAID MARKETS project in both Anambra and Ebonyi States. A total sample of 80 respondents (40 project farmers from each state) were selected using purposive and simple random sampling techniques. An interview schedule was used for data collection, while percentage and mean stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
4
7
0
Order By: Relevance
“…Greater household sizes provide free labour but subject to the willingness to support the family in its fish marketing. This result is in consonances with Nwalieji et al [2014] opined that large household size ensures availability of labour for marketing activities. This finding also supports the result of Anozie et al [2014] who reported that large household size compliment labour to enhance production and productivity thereby leading to increase in income.…”
Section: Resultssupporting
confidence: 88%
“…Greater household sizes provide free labour but subject to the willingness to support the family in its fish marketing. This result is in consonances with Nwalieji et al [2014] opined that large household size ensures availability of labour for marketing activities. This finding also supports the result of Anozie et al [2014] who reported that large household size compliment labour to enhance production and productivity thereby leading to increase in income.…”
Section: Resultssupporting
confidence: 88%
“…This is expected given the high labour requirement of rice farming and the low mechanization of farming in the study area. This is consistent with the findings of Nwalieji, et al [6] that rice farming is a male dominated enterprise.…”
Section: Socio-economic Characteristics Of Swamp Rice Farmerssupporting
confidence: 93%
“…The result indicates a large household size which can be a source of cheap labour both for the farm operations and the marketing services. This agrees with the findings of [16] and [15]. [21] opined that large household size ensures availability of labour for marketing activities.…”
Section: Household Sizesupporting
confidence: 92%
“…The mean age was approximately 36.0 years. This result implies that most of the OFSP marketers were within their middle, active and productive ages [15] and suggests that OFSP marketing business requires a lot of energy and is labour intensive, moving from one place to another to assemble the products for marketing and hawking. The result is in consonance with earlier studies by [16,17,18,19].…”
Section: Socio-economic Characteristics Of Respondentsmentioning
confidence: 99%